Linkage factors for sustainable indigenous tourism in Annah Rais, Bidayuh community, in Sarawak - Anak Ajis, Geraldine Joyce (2016)
In order to promote the sustainable indigenous tourism among the Bidayuh Community in Annah Rais in Sarawak, we should understand the linkage factors that influencing Bidayuh Community. The Bidayuh community is known as the „people of land‟ and well equipped with their cultural resources and has their own natural resources which attract the tourists to come to their place. Apart from that, this study also reveals on economic sustainability, socio-cultural sustainability and environmental sustainability which can help the community to participate in tourism activities and obstacles faced by them to develop tourism in their area. In addition to that, descriptive analysis was used to determine the level of linkage among the Bidayuh community. After finding that all the independent variables are correlated with the dependent variable, multiple regression analysis was conducted. The data has been analyzed and there were ten linking factors which were Padawan District Office, State Executive Council, Forestry Department and Land Survey, University Researcher, Community Leader, Sarawak Tourism Board, Travel Agency, Member of group or associations, Community and also NGO. Based on this study, 23 independent variables which were initially tested and there were three independent variables were predicted which consist of private government relations, stakeholders and education level. The most significant variables were private government relations, followed by education level and stakeholders. However, the development of tourism to expose the culture of the community in order to promote sustainable indigenous tourism to outsiders such as Sarawak Tourism Board, NGO is still questionable. The study shows that the Bidayuh community is willing to work with the government and involve in tourism to share their culture with outsiders.